Priorities for research in miscarriage: a priority setting partnership between people affected by miscarriage and professionals following the James Lind Alliance methodology. Issue 8 (23rd August 2017) - Prior, Matthew; Bagness, Carmel; Brewin, Jane; Coomarasamy, Arri; Easthope, Lucy; Hepworth-Jones, Barbara; Hinshaw, Kim; O'Toole, Emily; Orford, Julie; Regan, Lesley; Raine-Fenning, Nick; Shakespeare, Judy; et al.
Abstract : Objectives: To identify and prioritise important research questions for miscarriage. Design: A priority setting partnership using prospective surveys and consensus meetings following methods advocated by the James Lind Alliance. Setting: UK. Participants: Women and those affected by miscarriage working alongside healthcare professionals. Results: In the initial survey, 1093 participants (932 women who have experienced miscarriage, 8 partners, 17 family members, friends or colleagues, 104 healthcare professionals and eight charitable organisations) submitted 3279 questions. A review of existing literature identified a further 64. Non-questions were removed, and the remaining questions were categorised and summarised into 58 questions. In an interim electronic survey, 2122 respondents chose their top 10 priorities from the 58 summary questions. The 25 highest ranked in the survey were prioritised at a final face-to-face workshop. In summary, the top 10 priorities were ranked as follows: research into preventative treatment, emotional aspects in general, investigation, relevance of pre-existing medical conditions, emotional support as a treatment, importance of lifestyle factors, importance of genetic and chromosomal causes, preconception tests, investigation after different numbers of miscarriage and male causal factors. Conclusions: These results should be the focus of future miscarriage research. Presently, studies are being conducted to address the top priority; however, many other priorities, especially psychological and emotional support, are less well researched areas. We hope our results will encourage both researchers and funders to focus on these priorities.